Diagnosis of monogenic liver diseases in childhood by next‐generation sequencing. Issue 3 (12th December 2017) - Stalke, A.; Skawran, B.; Auber, B.; Illig, T.; Schlegelberger, B.; Junge, N.; Goldschmidt, I.; Leiskau, C.; von Neuhoff, N.; Baumann, U.; Pfister, E.‐D.
Abstract : Next‐generation sequencing (NGS) has opened up novel diagnostic opportunities for children with unidentified, but suspected inherited diseases. We describe our single‐center experience with NGS diagnostics in standard clinical scenarios in pediatric hepatology. We investigated 135 children with suspected inherited hepatopathies, where initially no causative pathogenic variant had been identified, with an amplicon‐based NGS panel of 21 genes associated with acute and chronic hepatopathies. In 23 of these patients, we detected pathogenic or likely pathogenic variants in 10 different genes. We present 6 novel variants. A total of 14 of these patients presented with the characteristic phenotype of the related hepatopathy. Nine patients showed only few or atypical clinical symptoms or presented with additional signs. In another 13 out of 135 cases, we detected variants of unknown significance (VUS) in 9 different genes. Only 2 of these patients showed characteristic phenotypes conclusive with the detected variants, whereas 11 patients showed unspecific or atypical phenotypes. Our multi‐gene panel is a fast and comprehensive tool to diagnose inherited pediatric hepatopathies. We also illustrate the challenge of dealing with genetic variants and highlight arising clinical questions, especially in patients with atypical phenotypes. Abstract :